PENGARUH SRATEGI DIVERSIFIKASI DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DIMODERASI OLEH CORPORATE GOVERNANCE (STUDI PADA PERUSAHAAN KELOMPOK LQ 45 DI BURSA EFEK INDONESIA TAHUN 2013- 2015) - Yenni Elmar; Amries Rusli Tanjung; Novita Indrawati (Jurnal Ekonomi, 2017)
The objectives of this research are to analyze and examine the effect of the diversification strategy and leverage on the firm value with corporate governance as a moderating variable. Business diversification is measured using the Herfindahl Index and leverage measured by using a Debt to Equity Ratio. The firm's value is measured using Tobin's Q ratio and corporate governance is measured by the Corporate Governance Score by IICD assessment for research carried out using the reference ASEAN Corporate Governance Scorcard relevant to the implementation of MEA in Indonesia. This study uses non-financial companies group LQ 45 listed in Indonesia Stock Exchange during 2013 to 2015 as a sample. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that the diversification strategy and leverage a negative effect on the value of the company. However, corporate governance moderates the relationship between diversification strategy and corporate value and can suppress the negative effects of diversification so that diversification becomes positive effect on firm value. While leverage relationships to firm value can not be moderated by corporate governance.